Saccharomyces boulardii in Acute Childhood Diarrhoea - Mandal, Anirban; Sahi, Puneet Kaur (Journal of Nepal Paediatric Society, 2018)
To the Editor, We read with much interest the article by Dash et al., published in the recent issue of your journal [1] but at the same time would like to make the following comments, clarification to which would benefit the general readers of JNPS.